2022
DOI: 10.21037/atm-22-2941
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNA in the serum of patients with polycystic ovary syndrome with insulin resistance

Abstract: Background: Polycystic ovary syndrome (PCOS) is the most common reproductive endocrine disease in women of childbearing age, and insulin resistance is an important etiological mechanism in PCOS. This study revealed the microRNA (miRNA) expression profile of PCOS with insulin resistance and explored the potential biological functions of differentially expressed miRNA.Methods: A total of 76 patients with PCOS and 30 normal healthy women were recruited in the gynecological clinic of the Second Hospital of Tianjin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…When compared to the normal control group and those receiving metformin treatment, the PCOS patient group in the current study demonstrated statistically signi cant increases in FBS, HbA1c, fasting insulin, HOMA-IR TC, TG, LDL, and testosterone while there was a signi cant decrease in HDL levels (p-value 0.05). In the same vein, (14) discovered that individuals with PCOS had signi cantly higher levels of (BMI), (T), (FBG), and (INS) of fasting insulin than did healthy controls (p0.05). Like how (15) con rmed our ndings, they discovered that the PCOS group had considerably lower levels of HDL, FSH, and E2 than the controls while signi cantly higher levels of BMI, fasting insulin, HOMA-IR, LDL, TG, TC, testosterone, and LH were present.…”
Section: Discussionmentioning
confidence: 92%
“…When compared to the normal control group and those receiving metformin treatment, the PCOS patient group in the current study demonstrated statistically signi cant increases in FBS, HbA1c, fasting insulin, HOMA-IR TC, TG, LDL, and testosterone while there was a signi cant decrease in HDL levels (p-value 0.05). In the same vein, (14) discovered that individuals with PCOS had signi cantly higher levels of (BMI), (T), (FBG), and (INS) of fasting insulin than did healthy controls (p0.05). Like how (15) con rmed our ndings, they discovered that the PCOS group had considerably lower levels of HDL, FSH, and E2 than the controls while signi cantly higher levels of BMI, fasting insulin, HOMA-IR, LDL, TG, TC, testosterone, and LH were present.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have shown that miRNAs play an important role in the development of PCOS, including the regulation of insulin resistance, inflammation, and ovarian function. 13 Among these miRNAs, the miR-17-92 cluster and miR-21 have been found to be dysregulated in PCOS patients. miR-17-92 cluster increases in the granulosa cells of PCOS patients, which may contribute to the development of follicular cysts.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Furthermore, miRNA-155 may contribute to the development of PCOS by disrupting normal ovarian function. 13,14 In addition to its role in ovarian function, miRNA-155 has also been implicated in inflammation and insulin resistance, two other key features of PCOS. miRNA-155 can promote inflammation and insulin resistance in various tissues throughout the body.…”
Section: Introductionmentioning
confidence: 99%